2020
DOI: 10.30886/estima.v18.936_in
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of living with a chronic wound: a meta-synthesis study

Abstract: Objective: explore qualitative research on the meanings of living with a chronic wound. Method: it is a qualitative meta-synthesis. 13 articles were included, totaling a sample of 248 individuals who self-reported living with a chronic wound. The Critical Appraisal Skills Program instrument was used to evaluate the eligible articles, and to report the qualitative synthesis, the recommendations of Enhancing transparency in reporting the synthesis of qualitative research were followed. The analysis and extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…23,24 For patients with CW, the primary dilemmas they confront are the direct and indirect repercussions of disease symptoms, treatment, and management, including ulcer and treatment-related pain; stigma and social isolation due to odor and exudate; activity restrictions (physical and social recreational activities) due to skin ulceration and wound dressing; dependence on family due to reduced self-care ability; anxiety about non-healing wounds; and fear of amputation. [25][26][27] Although no previous studies have explored the family resilience of patients with CW, relevant studies on family support of patients with CW suggest that family resilience has an impact on selfmanagement of patients with CW, because family resilience has been conceptualized as shared beliefs and support, strong family organization and positive interactions, and utilization of social resources, which are indicative of family support. 28 Wantonoro et al 19 concluded that strengthening the family support system for the management of diabetic ulcer care, such as improving family caregivers' knowledge and self-efficacy through interdisciplinary education, can positively affect the self-care of patients with wounds both physically and psychologically.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 For patients with CW, the primary dilemmas they confront are the direct and indirect repercussions of disease symptoms, treatment, and management, including ulcer and treatment-related pain; stigma and social isolation due to odor and exudate; activity restrictions (physical and social recreational activities) due to skin ulceration and wound dressing; dependence on family due to reduced self-care ability; anxiety about non-healing wounds; and fear of amputation. [25][26][27] Although no previous studies have explored the family resilience of patients with CW, relevant studies on family support of patients with CW suggest that family resilience has an impact on selfmanagement of patients with CW, because family resilience has been conceptualized as shared beliefs and support, strong family organization and positive interactions, and utilization of social resources, which are indicative of family support. 28 Wantonoro et al 19 concluded that strengthening the family support system for the management of diabetic ulcer care, such as improving family caregivers' knowledge and self-efficacy through interdisciplinary education, can positively affect the self-care of patients with wounds both physically and psychologically.…”
Section: Introductionmentioning
confidence: 99%
“…Uma ferida crônica é um dano na pele que ocorre com alterações duradouras na anatomia e fisiologia do local afetado durante o processo de regeneração tecidual. É uma condição que atinge todas as idades com implicações negativas na vida diária (Araújo et al, 2020).…”
Section: Introductionunclassified